2016
DOI: 10.31436/imjm.v15i1.415
|View full text |Cite
|
Sign up to set email alerts
|

‘I can’t pray’ – The spiritual needs of Malaysian Muslim patients suffering from depression

Abstract: Introduction: The mainstay of treatment of depression relies on pharmacological and psychological treatments. On top of that, evidence also recognizes the vital role of spirituality for human wellness which leads to growing interest in its utilization to treat depression. However, research on spirituality among Muslims in relation to depression is relatively scarce. The aim of this study is to explore the understanding of spirituality among Muslim patients with depression, and to explore their spiritual needs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To date, knowledge about these factors that might be applicable to Singapore's three dominant ethnic groups (Chinese, Malay, Indian) comes from research in other countries. For instance, regarding spiritual attitudes, research in Hong Kong found that Chinese adults ignored or stoically endured depression based on traditional fatalistic life views, 14 a Malaysian study described spirituality as an important coping mechanism for Malay adults experiencing depression, 15 whereas findings from Gujarat, India indicated that attributing depression to a religious cause was related to more pessimistic views about its outcome in Indian adults. 16 However, as Asian cultural representations of depression have been increasingly intertwined with Western views 17 and also depend on each nation's shared geo-cultural characteristics, it remains unclear to what extent the above ethnic differences still apply to Singapore.…”
Section: Introductionmentioning
confidence: 99%
“…To date, knowledge about these factors that might be applicable to Singapore's three dominant ethnic groups (Chinese, Malay, Indian) comes from research in other countries. For instance, regarding spiritual attitudes, research in Hong Kong found that Chinese adults ignored or stoically endured depression based on traditional fatalistic life views, 14 a Malaysian study described spirituality as an important coping mechanism for Malay adults experiencing depression, 15 whereas findings from Gujarat, India indicated that attributing depression to a religious cause was related to more pessimistic views about its outcome in Indian adults. 16 However, as Asian cultural representations of depression have been increasingly intertwined with Western views 17 and also depend on each nation's shared geo-cultural characteristics, it remains unclear to what extent the above ethnic differences still apply to Singapore.…”
Section: Introductionmentioning
confidence: 99%